Utilization of Biofloc System Catfish Pond Waste Nutrients in the Cultivation of Kale, Spinach, Pakcoy, and Lettuce Using the Aquaponic System - I Gusti Nyoman Arthanawa; I Nyoman Astiko; Dewa Putu Semara Yana; I Ketut Darmawan; Yohanes Parlindungan Situmeang (Scopus ID: 57189373733); I Dewa Nyoman Sudita (SEAS (Sustainable Environment Agricultural Science), 2021)
The cultivation of catfish using the biofloc system produces waste in the form of remaining ponds that can be used for aquaponic farming systems. The combination of fermentation between catfish waste and chicken manure affects the growth of kale, lettuce, pakcoy, and spinach with an aquaponic system. This research was conducted in the ALC (Agro Learning Center) garden in collaboration with the Master of Agricultural Science Study Program, Postgraduate Program of Warmadewa University. The parameters observed were plant height, number of leaves, fresh weight, and oven dry weight. The best results for plant height are found in spinach plants. The best number of leaves is found in pakcoy plants. As for fresh weight and dry weight the best results were on pakcoy plants. The best concentration of combination of catfish waste fermentation with chicken manure is at a concentration of 1400 ppm.